Caring for Pregnant Women for Whom Transfusion is Not an Option. A National Review to Assist in Patient Care. Issue 1 (March 2017) - Kidson-Gerber, Giselle; Kerridge, Ian; Farmer, Shannon; Stewart, Cameron L.; Savoia, Helen; Challis, Daniel
Abstract : (Aust N Z J Obstet Gynaecol. 2016;56(2):127–136) In situations where the administration of blood or blood products is not a therapeutic option, management of obstetric hemorrhage can be extremely difficult and require additional multidisciplinary communication as well as unique approaches. Transfusion may not be an option when a woman has complex red cell antibodies or a rare blood group, because blood products are unavailable, or because the patient refuses transfusion for religious (as in the case of Jehovah's Witnesses) or other reasons. In these circumstances, it is critically important that these women receive optimal management despite the inability to transfuse blood products. Research has shown that postpartum hemorrhage is the leading cause of maternal mortality and morbidity globally. A coordinated multidisciplinary approach, which may include blood products, is required in management of these situations.